Analýza a optimalizace současného stavu nakládání s odpady ve společnosti rPET InWaste s.r.o. - Dočekal, Petr (Vysoké učení technické v Brně. Fakulta chemická, 2024)
Tato diplomová práce se zabývá analýzou vybraných odpadů z výroby a návrhem vhodné optimalizace jejich nakládání v souladu s principy cirkulární ekonomiky a aktuální legislativy platné na území ČR. Dále se věnuje i optimalizaci nakládání s odpady vznikající v administrativních prostorech společnosti. Cílem práce bylo zpracování rešerše aktuálních legislativních a strategických dokumentů v oblasti odpadového hospodářství a v návaznosti na to následný návrh optimalizace pro vybrané toky odpadů. V experimentální části proběhla analýza vybraných odpadů z výrobní linky, kde byly použity metody FTIR, titrace a zahušťování. První část práce tvoří rešerše právních předpisů a strategických dokumentů na úrovni EU i ČR. Ve druhé části je navržena optimalizace nakládání s vybranými odpady. U některých z navržených řešení práce zhodnocuje ekonomickou rentabilitu navrhovaného řešení oproti konvenčním způsobům nakládání s odpady. Výsledky a použité metody vedly k návrhu optimalizace nakládání s odpady ve výrobě i v administrativní části podniku rPET InWaste s.r.o.

This master's thesis deals with the analysis of selected waste from production and the proposal of appropriate optimization of their management in accordance with the principles of circular economy and current legislation in force in the Czech Republic. It also deals with the optimization of waste management arising in the administrative premises of the company. The aim of the work was to prepare a research of current legislative and strategic documents in the field of waste management and, in connection with this, a subsequent proposal for optimization for selected waste streams. In the experimental part, analysis of selected waste streams from the production line was carried out using FTIR, titration and vacuum evaporation methods. The first part of the thesis consists of the research of legal regulations and strategic documents in the EU and Czech republic. In the second part, the optimization of selected waste management is proposed. For some of the proposed solutions, the thesis evaluates the economic viability of the proposed solution compared to conventional management methods. The results and the methods used led to the proposal of optimization of waste management in production and administrative part of the company rPET InWaste s.r.o.
Analysis and optimization of the current state of waste management in rPET InWaste s.r.o.
Keywords: odpad; optimalizace; analýza; oběhové hospodářství; PET; waste; optimization; analysis; circular economy; PET